Characteristics of phosphate sorption and sorbed-P release in paddy soils - HE Song-duo; ZHANG Qi-chun; WANG Guang-huo (浙江大学学报. 农业与生命科学版, 2010)
Characteristics of phosphate sorption and sorbed-P release in paddy soils were studied using adsorption isotherm and ion exchange resin method. The results show that phosphate adsorption isotherm of 20 rice soils of Jinhua City of Zhejiang Province fitted in with Langmuir equation very well. The correlation coefficients were from 0.970 to 0.999. Parameters of Xm, X0.2, K and MBC (maximum buffer capacity) of the Langmuir equation might correlate with soil properties. The highest values of Xm, K, MBC and X0.2 were found in red earth derived rice soils, which might relate to their high content of clay and Fe, Al oxides. Comparing with upland crops, which equilibrium P concentration of 0.2 mg·L-1 may satisfy P demand for most crops, irrigated rice might need a less equilibrium P concentration in solution for its growth because the solution P could be more easily compensated through P release from soil particles in rice soils. It was found that the resin extractable P was proportional to soil adsorbed P (sum of soil Resin-P and newly adsorbed P from solution). The linear relationship was valid for all the soils studied, that is RAQ P=A+BX, where A and B are constants (r=0.941 to 0.999). It seemed that under water submerged condition, phosphate adsorbing saturation controlled the rate and quantity of P released from soil to the resin sink. Thus, for P fertilizer management in paddy soils, it pay our attention to maintain an adequate level of total soil P content or to maintain an adequate level of soil available P.